Recent advances in metal-organic frameworks for therapeutic applications in periodontitis - Chen, Jiaqi; Bai, Yang; Ding, Yude; Wang, Linhong; Zhang, Wentao; Yang, Fan (Frontiers in Medicine, 2025)
Periodontitis is a highly prevalent chronic inflammatory disease that leads to the destruction of periodontal tissues and has systemic health implications. Current treatments, such as mechanical debridement and antibiotics, are often inadequate due to poor biofilm penetration, drug resistance, and limited regenerative capacity. Metal-organic frameworks (MOFs) have recently emerged as a transformative platform to address these limitations and surpass traditional nanomaterials (e.g., liposomes, dendrimers). Their tunable porosity, multifunctional composition, and responsive degradation enable antibacterial, anti-inflammatory, and pro-regenerative actions. This review highlights the mechanisms by which MOFs combat periodontal pathogens, resolve inflammation, and promote tissue regeneration, outperforming conventional materials. We also discuss combinatorial strategies, such as photodynamic and immunomodulatory therapies, that enhance treatment efficacy. Despite promising preclinical results, challenges in biocompatibility, biodegradation, and clinical translation remain. Future efforts should focus on developing intelligent, multifunctional MOF platforms capable of microenvironment-responsive therapy to achieve complete periodontal restoration.